De novo genetic variation revealed in somatic sectors of single Arabidopsis plants [v2; ref status: indexed, http://f1000r.es/1ii] - Marianne T Hopkins; Aaron M Khalid; Pei-Chun Chang; Karen C Vanderhoek; Dulcie Lai; Meghan D Doerr; Susan J Lolle (F1000Research, 2013)
Concern over the tremendous loss of genetic diversity among many of our most important crops has prompted major efforts to preserve seed stocks derived from cultivated species and their wild relatives. Arabidopsis thaliana propagates mainly by self-fertilizing, and therefore, like many crop plants, theoretically has a limited potential for producing genetically diverse offspring. Despite this, inbreeding has persisted in Arabidopsis for over a million years suggesting that some underlying adaptive mechanism buffers the deleterious consequences of this reproductive strategy. Using presence-absence molecular markers we demonstrate that single Arabidopsis plants can have multiple genotypes. Sequence analyses reveal single nucleotide changes, loss of sequences and, surprisingly, acquisition of unique genomic insertions. Estimates based on quantitative analyses suggest that these genetically discordant sectors are very small but can have a complex genetic makeup. In ruling out more trivial explanations for these data, our findings raise the possibility that intrinsic drivers of genetic variation are responsible for the targeted sequence changes we detect. Given the evolutionary advantage afforded to populations with greater genetic diversity, we hypothesize that organisms that primarily self-fertilize or propagate clonally counteract the genetic cost of such reproductive strategies by leveraging a cryptic reserve of extra-genomic information.